Analyzing the Efficiency of Dairy Production in the Philippines - Hernandez, Hannah Ericka; Mercado, Thea Elaine; Sobremonte, Emee Marie; Rosete, Marie Antoinette (IJOSMAS, 2022)
The efficiency of the dairy industry in the Philippines is determined by the sector’s productivity in relation to investments, imports, and exports that it is making. The use of Total Factor Productivity (TFP) in this paper is to examine the connection between the dependent variable and independent variables. More so, this research aims to evaluate the efficiency of the dairy industry along with the objective of assessing the impact that investments, imports, and exports have. Quarterly data from 2006 to 2017 helps to obtain results and use for further interpretation using regression analysis. The study shows that investments, imports, and exports do affect the productivity of the dairy industry in the Philippines. It leads to rejecting the null hypothesis in this paper. The research findings may address these issues by giving attention to exports and investments mainly to machineries and other technologies that contribute to dairy operations. The researchers also recommend that to be able to improve productivity, investments, imports, and exports of the dairy industry, the government should provide more funding and assistance to dairy farmers. Keywords: Investments, Imports, Exports, Productivity, Efficiency, Dairy